E-Health Applications Support Medication Adherence in Coronary Heart Disease Patients: Aplikasi E-Health Mendukung Kepatuhan Minum Obat pada Pasien Penyakit Jantung Koroner - Wahananingtyas, Nova Listya; Bakar, Abu; Harmayetty, Harmayetty (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Coronary heart disease (CHD) is a leading cause of mortality, with medication adherence being critical for effective management. However, adherence remains low, necessitating innovative solutions. Specific Background: E-health applications offer features such as reminders, education, and remote monitoring to enhance adherence. Knowledge Gap: While e-health is widely used, its effectiveness in improving medication adherence among CHD patients requires further evaluation. Aims: This study systematically reviews the effectiveness of e-health applications in enhancing CHD medication adherence and identifies key influencing factors. Results: Findings suggest that e-health applications improve adherence through digital education, reminders, and family support. Challenges include digital literacy gaps, economic constraints, and privacy concerns. Novelty: This review synthesizes current evidence, highlighting benefits, challenges, and strategies for optimizing e-health adoption. Implications: Strengthening digital infrastructure, patient education, and data security policies is essential to maximize the impact of e-health in CHD management. Highlights: E-health applications improve medication adherence through reminders, education, and remote monitoring. Challenges include digital literacy gaps, privacy concerns, and economic barriers that hinder widespread adoption. Comprehensive strategies such as digital infrastructure improvement and patient education are essential for effective implementation. Kewywords: E-Health, Medication Adherence, Coronary Heart Disease, Digital Health, Patient Compliance